PERANCANGAN SISTEM POMPA AIR DENGAN MEMANFAATKAN PLTS 20 KWP DESA TIANYAR TENGAH - Bima Aditya Putra; I Wayan Sukerayasa; Cok Gede Indra Partha (Jurnal SPEKTRUM, 2020)
Implementation of solar power plants in Bali, located in Karangasem Regency, Bali Province. In 2013, the Ministry of Energy and Mineral Resources built a 15 kWp and 20 kWp off grid small scale solar power plants pilot project in Tianyar Village, Kubu District, Karangasem Regency. 20 kWp Central Tianyar solar power plants and 15 kWp West Tianyar currently abandoned unused, Therefore in this study it will be discussed more deeply about 20 kWp solar power plants in Tianyar Village to optimize the use of solar power plants in tianyar village as a source of water pump drive. Designing a Water Pump System Using the 20 kWp solar power plants of Central Tianyar Village has a total Head Losses of 109,519 m, the pump used is 1 LEO 4XRm6 / 20-2.2 water pump with an average head of 110 m. The pipe used is a PVC pipe along the 1640 m with a diameter of 2 Inch. This design also uses 6 Elbow fittings, 90 ° Threaded Regular. The need for drinking and cooking water that is needed by residents of Tianyar Tengah Village Banjar Bukit Lambuh is 38,880 liters / day. This design can lift water needs of 38,400 liters / day or as much as 98.76% or as many as 1279 out of 1296 people who are met the need for clean water for drinking and cooking.